2012
DOI: 10.1111/j.1742-481x.2012.00956.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence‐based practice standards for the use of topical pressurised oxygen therapy

Abstract: Whenever a new therapy enters the wound care arena it is mandatory to deliver the best evidence to clinicians, healthcare administrators and policy makers to support integration of the technology into clinical practice. While this can often be problematic when novel therapies lack a large body of supporting evidence, methods that incorporate the use of expert opinion do exist to evaluate existing evidence and create consensus statements that can help guide decisions. Topical pressurised oxygen therapy is a met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 8 publications
(40 reference statements)
1
21
0
Order By: Relevance
“…71 The lack of a formal study in this regard has been offset by several reviews, case series, and experimental studies on the effect of topically administered oxygen at the wound surface that seem to indicate a benefit in promoting wound repair. 154,[159][160][161][162][163][164][165][166][167][168][169] While several RCTs with different devices have been ongoing, there have been no publications to date comparing 12-week healing rates with those of standard care.…”
Section: Negative Pressure Wound Therapymentioning
confidence: 99%
“…71 The lack of a formal study in this regard has been offset by several reviews, case series, and experimental studies on the effect of topically administered oxygen at the wound surface that seem to indicate a benefit in promoting wound repair. 154,[159][160][161][162][163][164][165][166][167][168][169] While several RCTs with different devices have been ongoing, there have been no publications to date comparing 12-week healing rates with those of standard care.…”
Section: Negative Pressure Wound Therapymentioning
confidence: 99%
“…For example, the use of oxygen under pressure or "hyperbaric oxygen therapy" (HBO 2 ) was shown to have a positive effect on ischemia and local wound hypoxia (4)(5)(6). In the last few years, additional medical procedures that allow topical administration of oxygen therapy directly to the wound site in order to support wound healing have been developed (7)(8)(9). One of the major complications affecting wound healing are infection, many of which are caused by multidrug-resistant pathogens and surface-associated (biofilm) bacteria (1,(10)(11)(12).…”
mentioning
confidence: 99%
“…2 In 2005 the Undersea and Hyperbaric Medicine Society (UHMS) published a position statement regarding TOT use in chronic wounds and concluded that ''topical oxygen as a therapeutic strategy in wound healing is not adequately supported by scientific data.'' 3 A number of studies have been published so far.…”
Section: Introductionmentioning
confidence: 99%